First, divide each side of the equation by #color(red)(2)# to eliminate the #parenthesis while keeping the equation balanced:
#S/color(red)(2) = (2(wl + wh + lh))/color(red)(2)#
#S/2 = (color(red)(cancel(color(black)(2)))(wl + wh + lh))/cancel(color(red)(2))#
#S/2 = wl + wh + lh#
Next, subtract #color(red)(lh)# from each side of the equation to isolate the #w# terms while keeping the equation balanced:
#S/2 - color(red)(lh) = wl + wh + lh - color(red)(lh)#
#S/2 - lh = wl + wh + 0#
#S/2 - lh = wl + wh#
Then, factor a #w# from each term on the right side of the equation giving:
#S/2 - lh = w(l + h)#
Now, divide each side of the equation by #color(red)((l + h))# to solve for #w# while keeping the equation balanced:
#(S/2 - lh)/color(red)((l + h)) = (w(l + h))/color(red)((l + h))#
#(S/2)/color(red)((l + h)) - (lh)/color(red)((l + h)) = (wcolor(red)(cancel(color(black)((l + h)))))/cancel(color(red)((l + h)))#
#S/(2(l + h)) - (lh)/(l + h) = w#
#w = S/(2(l + h)) - (lh)/(l + h)#
We can also rewrite this as:
#w = S/(2(l + h)) - (2/2 xx (lh)/(l + h))#
#w = S/(2(l + h)) - (2lh)/(2(l + h))#
#w = (S - 2lh)/(2(l + h))#